Self-Reported Measures Have a Stronger Association With Dizziness-Related Handicap Compared With Physical Tests in Persons With Persistent Dizziness - Kristiansen, Lene; Magnussen, Liv H.; Wilhelmsen, Kjersti T.; Maeland, Silje; Nordahl, Stein Helge G.; Hovland, Anders; Clendaniel, Richard; Boyle, Eleanor; Juul-Kristensen, Birgit (Frontiers in Neurology, 2022)
Background: People with persistent dizziness have presented a variety of symptoms and characteristics influencing daily activities. However, there seems to be little evidence on a broad profile (i.e. physical, psychological, and “other” characteristics) and their relative association with dizziness-related handicap. Objective: To describe a broad profile of physical, psychological, and “other” characteristics in people with persistent dizziness across three severity levels of the Dizziness Handicap Inventory (DHI) and investigate their relative associations with the DHI. Method: Participants with persistent dizziness (n=107) were included in this cross-sectional study. The participants underwent a physical therapy examination and completed questionnaires about characteristics across three domains: 1) physical (normal and fast gait velocity, grip strength, flexibility, and movement-induced dizziness intensity), 2) psychological (Mobility Inventory of Agoraphobia, Body Sensation Questionnaire, Agoraphobic Cognitions Questionnaire, and Hospital Depression and Anxiety Questionnaire) and 3) “other” (Vertigo Symptom Scale, Chalders Fatigue Scale, and EQ visual analog scale), in addition to the DHI questionnaire. Data were presented by descriptive statistics for the three DHI severity levels. A multiple linear backward regression analysis was conducted for each domain, with additional analyses adjusting for age and sex. Based on these results, significant associations were tested in a final regression model. Results: With increasing severity levels of DHI, the participants demonstrated worse performance on most of the physical characteristics (preferred and fast gait velocity, dizziness intensity after head movements), all psychological characteristics (avoidance behavior, fear of bodily sensation, fear of fear itself, psychological distress), and most of the “other” characteristics (fatigue, dizziness severity, quality of life). After adjusting for age and sex significant associations were found between total DHI and psychological (avoidance behavior, psychological distress) and “other” (dizziness severity and quality of life) domains, but not with the physical domain, explaining almost 60% of the variance of the DHI total score. Conclusion: There was a trend towards worse scores of each characteristic in relation to an increasing DHI severity level. However, final analyses showed that DHI was only associated with psychological and “other” characteristics, and not the physical. In clinical assessments and treatment of this patient group, all characteristics should, however, be considered.